THE ROSS OROGENY OF THE TRANSANTARCTIC MOUNTAINS: A NORTHERN VICTORIA LAND PERSPECTIVE - Federico L.; Capponi G.; Crispini L. (My University, 2006)
Northern Victoria Land (Antarctica) is made up of three terranes of Cambrian–Ordovician rocks: the Wilson (WT), Bowers (BT) and Robertson Bay terranes (RBT). The WT comprises a low- to high-grade metasedimentary sequence intruded by calc-alkaline plutons with magmatic arc affinity; the BT is composed of low-grade metavolcanic and metasedimentary rocks usually interpreted as an intra-oceanic arc; the RBT is a very low-grade flysch-like sequence. Terrane juxtaposition has traditionally been attributed to accretion during the Cambro-ordovician Ross orogeny. We propose a new model in which the WT, BT and RBT are interpreted as an arc/back-arc/trench system, developed in the context of a SW-dipping subduction zone. The subducting plate carried a continent originally located outboard of the turbidite fan of the RBT. Collision between this continent and the East Antarctic craton caused partial subduction of the intervening back-arc basin and, ultimately, the end of Ross-orogenic subduction. The turbidite fan of the RBT originally sedimented above the trench and on the subducting oceanic plate; due to collision it was thrusted on the continent, that constitutes, at least in part, the present basement of the RBT turbidite. The eastern portions of this continental mass were later dissected by the tensile tectonics related to the opening of the of the Southern Ocean.
Keywords: BACK-ARC; CAMBRO-ORDOVICIAN; ROSS OROGENY; NORTHERN VICTORIA LAND; ANTARCTICA; Ordovician; Cambrian; Paleozoic::Ordovician; Палеозой::Ордовикская; Paleozoic::Cambrian; Палеозой::Кембрийская